Global Scaling Up Sanitation Project : Training and Capacity Building to Scale Up Rural Sanitation - World Bank (Washington, DC, 2012)
The Water and Sanitation Program's (WSP's) Global Scaling up Sanitation Project combines the approaches of Community-Led Total Sanitation (CLTS), behavior change communications, and social marketing to generate sanitation demand and strengthen the supply of sanitation products and services at large scale. Training has played an essential role to scale up rural sanitation in India, Indonesia, and Tanzania, where the project has been implemented to date. Two key learning's have emerged. First, training skills are essential at all levels (national, regional, and local) to implement an at-scale rural sanitation program; and second, a training program must focus at the local government level for implementation.